Characteristics Of Archaic Syncretism in Uzbek Ethno-Culture and National Culture and Their Effects (Eurasian Journal of Humanities and Social Sciences, 2023)
In this article, the characteristics of archaic syncretism and their influence in Uzbek ethnocultural and national culture are revealed in a scientific-analytical, scientificdiscussive way. In this, the syncretic features, important signs and social significance of the processes related to archaic syncretism in the Uzbek ethnoculture and national culture are expressed in a scientific and analytical way